Scientific and methodological support of the work of the department of sociology of the faculty of philosophy and social sciences of the Belarusian State University - Kurilovich, Natalia V. (Journal of the Belarusian State University. Sociology, 2025)
The content of the concept «scientific and methodological support of education» is revealed. The interrelation between this aspect of education and the improvement of the quality of education in higher education institutions is emphasised. The question of transformation of the legislative base in the sphere of higher education of the Republic of Belarus is actualised. The article considers the following indicators of scientific and methodological support of the work of the department of sociology of the faculty of philosophy and social sciences of the Belarusian State University: development and approval of educational programme documentation, preparation of scientific and educational publications, electronic educational and methodological complexes for academic disciplines, as well as participation of the teaching staff in scientific and methodological conferences.